(untitled) (Palíndromo, 2013)
Fire in museum (2010), art intervention by the argentine artist Cristian Segura offers the visitor a different way to look at the museum. The artist uses the device simulacra, designed by Jean Baudrillard (1997), to trigger other experiences, such as an imminent fire. Thus, Cristian Segura’s images of destruction are pure images without reverse, without perspective, without illusion or intention to create another reality, because they belong to their own domain. For Cristian, every work is a new possibility to perceive the spaces forgotten by city and question the problems of art institutions, not seeking a representation of a sentimental past or future, but mocking the urban spaces and museums.